2022
DOI: 10.1590/1414-431x2022e12194
|View full text |Cite
|
Sign up to set email alerts
|

Determination of glyphosate in breast milk of lactating women in a rural area from Paraná state, Brazil

Abstract: The aim of this study was to verify the presence of glyphosate in breast milk and to characterize maternal environmental exposure. Sixty-seven milk samples were collected from lactating women in the city of Francisco Beltrão, Paraná, living in urban (n=26) and rural (n=41) areas, at the peak of glyphosate application in corn and soy crops in the region (April and May 2018). To characterize the study population, socio-epidemiological data of the women were collected. To determine glyphosate levels, a commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Our findings strengthen several worldwide studies demonstrating augmented breast cancer risk in pesticide occupationally exposed women (47)(48)(49)(50)(51)(52)(53)(54)(55) by adding information about possibly implicated mechanisms in the pre-carcinogenic stages. Detecting pesticides in urine, blood, breast milk, and mammary tissue samples from exposed women reinforces the idea that they may have a systemic impact (14,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 66%
“…Our findings strengthen several worldwide studies demonstrating augmented breast cancer risk in pesticide occupationally exposed women (47)(48)(49)(50)(51)(52)(53)(54)(55) by adding information about possibly implicated mechanisms in the pre-carcinogenic stages. Detecting pesticides in urine, blood, breast milk, and mammary tissue samples from exposed women reinforces the idea that they may have a systemic impact (14,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 66%
“…Studies have shown that glyphosate and AMPA are present in the bodies of the population, indicating a collective health problem. Examples include the studies by Palma et al [ 30 ] and Camiccia et al [ 31 ], which detected glyphosate in breast milk samples from infants in the Midwest and South of Brazil, respectively, demonstrating that babies are also vulnerable, despite having developing immune systems.…”
Section: Glyphosate Usementioning
confidence: 99%
“…Adapted from [18,19]. References (water [26,[29][30][31][32][33], food [13,[34][35][36], and humans [37][38][39]).…”
Section: Figurementioning
confidence: 99%